The Integral Healer: The 4 Pillars of the Healer's Practice - James D Duffy MD, FANPA, FAAHPM, DABMA (SAGE Publishing, 2020)
The scientific method has provided the 21st allopathic healer with many powerful and effective tools to combat disease. However, the management of technology does not equate with being a healer. The integral healer not only utilizes the power of the scientific method but also balances its application with compassionate intention and wise perspective. This article describes the characteristics of the 4 pillars of becoming an integral healer (competency, compassion, wisdom, and self-cultivation) and describes how each one of these pillars is vital to being a healer.